WAKAMONO KOTOBA DALAM MANGA AIR GEAR VOLUME 1-5 KARYA OH! GREAT - Hapsari Julianita, Putu Raditya (Humanis; Volume 15. No.1. April 2016)
Air Gear is a Japanese manga created by Oh! Great. This manga is the best Japanese manga for shonen (boys) in 2006. Japanese manga in general uses young characters so that the author mixed up his manga with action, comedy, and technology. In his manga, there are roller blades known as Air Track which is very famous shoes on the manga. The purpose of this research is to find wakamono kotoba. Wakamono kotoba is word that usually use by youth in Japan and every time the word will change. This research found the formations, the functions and the meanings of wakamono kotoba. Those words are made up from an unique form and use to express themselves and their feeling. According to the result of analysis, those words have some formations, functions and meanings of wakamono kotoba. These words refer to how the Japanese formal word could change to informal word like wakamono kotoba.
Keywords: wakamono kotoba, formation, function, meaning